Pembelajaran keterampilan musikal pada siswa kelas IV sekolah dasar dengan menggunakan media audio visual - Sopian; Sukma Murni; Febri Restu Widianto (IKIP Siliwangi, 2023)
This study aims to examine the learning of musical skills in grade IV students using audio-visual media. The research method used is descriptive qualitative. The subjects in this study were fourth grade students of SD Negeri 195 Isola Kota Bandung with a total of 34 students consisting of 17 male students and 17 female students. The instruments used were teacher and student observation sheets, evaluation questions, and teacher and student questionnaires. The results showed that there was an increase in the quality of learning after using audio visual media. This is indicated by the average value of class musical skills of 76.32 which is in the good category, the highest score of students is 90 and the lowest score is 60. Students' learning completeness shows 94.1% of students get scores above the minimum completeness criteria and 5, 9% still scored below the minimum completeness criteria value.Â